2017
DOI: 10.15171/jrip.2018.47
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide metabolite changes in gentamicin-induced nephrotoxicity; the effects of antioxidant vitamins

Abstract: In this experimental study, 68 adult Wistar rats made the subject of the study. Administration of vitamin E and C, in an individual manner, can have some more favorable effects on urea, creatinine and nitrite level in GM nephrotoxicity than their coadministration. On the other hand, there is a gender difference, in response to vitamin E and C in which male gender responded more favorably to the antioxidant vitamins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…The same results were obtained when we evaluated the effects of both CAR and DIC on the nitrite level of rats and we found that DIC could elevate the level of nitrite in rats. This finding was in total agreement with the previous results disclosed that NO plays a vital role in DIC-induced damage [ 42 , 43 ]. Moreover, we found that CAR could remarkably diminish the levels of NO in DIC-treated rats, shedding another light on the anti-oxidant property of the agent.…”
Section: Discussionsupporting
confidence: 94%
“…The same results were obtained when we evaluated the effects of both CAR and DIC on the nitrite level of rats and we found that DIC could elevate the level of nitrite in rats. This finding was in total agreement with the previous results disclosed that NO plays a vital role in DIC-induced damage [ 42 , 43 ]. Moreover, we found that CAR could remarkably diminish the levels of NO in DIC-treated rats, shedding another light on the anti-oxidant property of the agent.…”
Section: Discussionsupporting
confidence: 94%
“…Increase in level of nitrite in DIC-only treated rats indicated the effect of NO in liver toxicity induced by DIC. Our results are in line with the prior studies that have shown NO creates important role in chemical toxicity (32,33). Remarkable reduction of nitrite content in silymarin treated groups suggested that this antioxidant offered liver protection in DIC exposed rats by reduce the NO content and nitrosative stress.…”
Section: Discussionsupporting
confidence: 92%
“…In this vein, previous investigations also suggested that DIC engages NO for exerting its devastating effects on the organs. 34,38 Notable diminutions of nitrite level in DIC plus QR treated group implied that this agent exerted renal protection in DIC exposed animals through the diminution of NO levels and nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%